Governing HPV-related carcinoma using vaccines: Bottlenecks and breakthroughs - Bhattacharjee, Rahul; Kumar, Lamha; Dhasmana, Archna; Mitra, Tamoghni; Dey, Abhijit; Malik, Sumira; Kim, Bonglee; Gundamaraju, Rohit (Frontiers in Oncology, 2022)
Human papillomavirus (HPV) contributes towards sexually transmitted infection which is primarily associated with pre-cancerous and cancerous lesions in both men as well as women and is amongst the neglected cancerous infections in the world. Till date, two kinds of vaccines either preventive or therapeutic are available to combat the HPV infection. Around the world, three preventive HPV vaccines targeting high-risk HPV strains are available: 2-, 4, and 9-valent vaccines which are constituted from pure L1 protein that self-assembles into HPV type-specific empty shells using recombinant DNA technology. Therapeutic vaccines are produced by early and late onco-proteins impart superior cell immunity than preventative vaccines. In the current review, we have not only discussed the clinical significance and the importance of both preventative and therapeutic vaccines but also highlighted dosage and mode of administration for them. This review is novel in its way as it will pave the way for researchers to address the challenges posed by HPV based vaccines in present time.